2019
DOI: 10.1111/jce.14103
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic basal crux ventricular arrhythmias with left bundle branch block and superior axis: A comparison with inferior‐septal valvular arrhythmias

Abstract: Introduction Left bundle branch block (LBBB) with superior axis is common in patients with idiopathic‐ventricular arrhythmia (VA) originating from the tricuspid annulus (TA) and rarely from the cardiac basal crux and mitral annulus (MA). We described the electrocardiography and electrophysiological findings of idiopathic‐VA presenting with LBBB and superior axis. Methods and Results We described 42 idiopathic‐VA patients who had an LBBB and superior axis; 15 basal crux‐VA, 17 TA‐VA, and 10 MA‐VA. No patient ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Previous studies have reported the ECG characteristics of MA-VAs in patients without structural heart disease as the following: right bundle branch block pattern (RBBB), S or s waves in lead V6, and an early precordial transitional zone < V2 [ 7 , 8 ]. After that, many studies focused on ECG characteristics and RFCA of VAs originating from specific areas adjacent to the MA [ 9 , 10 , 11 , 12 , 13 , 14 ]. However, few have systematically analyzed VA’s ECG characteristics originating from both epicardial and endocardial areas adjacent to the MA.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the ECG characteristics of MA-VAs in patients without structural heart disease as the following: right bundle branch block pattern (RBBB), S or s waves in lead V6, and an early precordial transitional zone < V2 [ 7 , 8 ]. After that, many studies focused on ECG characteristics and RFCA of VAs originating from specific areas adjacent to the MA [ 9 , 10 , 11 , 12 , 13 , 14 ]. However, few have systematically analyzed VA’s ECG characteristics originating from both epicardial and endocardial areas adjacent to the MA.…”
Section: Introductionmentioning
confidence: 99%